Optimasi Sistem Pemesanan Kuliner Berbasis Web Menggunakan QR Code pada ABC Billiard - Annata Rosiona; Nazarul Ikhitiar; Aqiella Jamo Nezzar; Joko Suwarno (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Operational activities in the culinary sector require fast, accurate, and efficient services to maintain customer satisfaction and improve service quality. ABC Billiard currently applies a conventional food and beverage ordering process using handwritten order notes, which often results in order recording errors, delays in delivering order information to the kitchen, and longer service times during peak operating hours. In addition, the manual transaction recording process makes it difficult for management to monitor sales activities and generate accurate reports in a timely manner. To address these issues, this study designs and develops a web-based food and beverage ordering information system integrated with QR Code technology as a digital menu access medium. The software development process adopts the Agile methodology with the Scrum framework due to its flexibility in accommodating changing user requirements throughout the development stages. Data were collected through direct observation, interviews with the business owner and operational staff, and a literature review to identify the system requirements based on actual business conditions. The resulting system enables customers to independently access the digital menu by scanning a QR Code using their smartphones without waiting for waiters. Orders are automatically transmitted in real time to both the kitchen and cashier dashboards, thereby improving service efficiency and reducing communication delays. The implementation of the proposed system minimizes the risk of order recording errors, accelerates the ordering process, simplifies transaction data management, and provides centralized real-time sales information that supports managerial decision-making and enhances the overall operational performance of ABC Billiard.